DISLOCATIONS MOBILITY UNDER THE IMAGE FORCE EFFECT IN BICRYSTALS OF CFC MATERIALS: CU-X, X = PB, AL, AU, AG AND NI (Journal of Sciences & Technology, 2017)
The image force undergone by a matrix dislocations close and parallel to an interphase boundary is studied in Cu-X bicrystals (with X = Pb, Al, Au, Ag, Ni) for disorientations ranging between 0° and 90°.  Dislocations have a Burgers vector  = a/2 [110]. The elastic energy of dislocation-boundary interaction is calculated within the framework of anisotropic linear elasticity. The elastic energy is related to the difference of the two metals shear moduli. It is about a few hundred pico Joule per meter. The image force can be repulsive or attractive according to the sign and the intensity of shear moduli difference. The isoenergy maps have various symmetries according to the disorientation.